Analysis of the Influence of Savings and Loans Products and Service Quality on Loyalty and the Role of Satisfaction as a Moderation Variable - Koidatul Nurulaeni; Wahju Wulandari; Nasharuddin Mas (Journal of Management Research and Studies, 2024)
The purpose of this research is to determine the effect of savings and loan products and service quality on customer loyalty which is moderated by customer satisfaction in the study of KPRI Yustisia customers at the Malang District Court. The sampling technique in this research uses "Non Probability Sampling", and the sampling method in this research is "Saturated Sample" (Total Sampling) of 73 KPRI Yustisia customers. Data is processed via Smart Partial Least Square (PLS) software. The research results show that savings and loan products do not have a significant effect on customer loyalty. Service quality does not have a significant effect on customer loyalty. Customer satisfaction has a negative and significant effect on customer loyalty. Customer satisfaction does not play a role in moderating the influence of savings and loan products on customer loyalty. Customer satisfaction does not play a role in moderating service quality on customer loyalty.